Single-Center Experience With Protocolized Treatment of Left Ventricular Assist Device Infections - Verkaik, Nelianne J.; Yalcin, Yunus C.; Bax, Hannelore I.; Constantinescu, Alina A.; Brugts, Jasper J.; Manintveld, Olivier C.; Birim, Ozcan; Croughs, Peter D.; Bogers, Ad J. J. C.; Caliskan, Kadir (Frontiers in Medicine, 2022)
Purpose Because of the current lack of evidence-based antimicrobial treatment guidelines, Left Ventricular Assist Device (LVAD) infections are often treated according to local insights. Here, we propose a flowchart for protocolized treatment, in order to improve outcome. Methods The flowchart was composed based on literature, consensus and expert opinion statements. It includes choice, dosage and duration of antibiotics, and indications for suppressive therapy, with particular focus on Staphylococcus aureus (SA) (Figure 1). The preliminary treatment results of 28 patients (2 from start cephalexin suppressive therapy) after implementation in July 2018 are described. Results Cumulative incidence for first episode of infection in a 3-year time period was 27% (26 of 96 patients with an LVAD). Twenty-one of 23 (91%) first episodes of driveline infection (10 superficial and 13 deep; nine of 13 caused by SA) were successfully treated with antibiotics according to flowchart with complete resolution of clinical signs and symptoms. For two patients with deep driveline infections, surgery was needed in addition. There were no relapses of deep driveline infections, and only 2 SA deep driveline re-infections after 6 months. Nine patients received cephalexin of whom four patients (44%) developed a breakthrough infection with cephalexin-resistant gram-negative bacteria. Conclusions The first results of this protocolized treatment approach of LVAD infections are promising. Yet, initiation of cephalexin suppressive therapy should be carefully considered given the occurrence of infections with resistant micro-organisms. The long-term outcome of this approach needs to be established in a larger number of patients, preferably in a multi-center setting.